Outcome of Botulinum Toxin Therapy for Management of Chronic Anal Fissure: A Prospective Study of 60 Patients - Islam, Md Shohidul; Hossain, Md Anowar; Ara, Mst Iffat (Journal of Rangpur Medical College, 2026)
Background: Chronic anal fissure (CAF) is a common anorectal disorder characterized by severe pain during defecation and impaired quality of life. While lateral internal sphincterotomy remains the standard treatment, it carries the risk of incontinence. Botulinum toxin (BTX) injection has emerged as a minimally invasive alternative. Objective: To evaluate the efficacy and safety of BTX therapy in the management of CAF in a cohort of 60 patients. Methods: This prospective study included 60 patients diagnosed with CAF at department of colorectal surgery, Bangladesh Medical University from January 2024 to December 2025. BTX-A was administered via injection into the internal anal sphincter. Patients were followed for 12 weeks, with outcomes assessed in terms of pain relief, fissure healing, and adverse events. Results: Complete fissure healing was observed in 46 (76.7%) patients, while 10 (16.7%) showed partial healing, and 4 (6.6%) showed no response. Significant reduction in pain scores was reported at 2,4, and 8weeks post-treatment. Minor adverse events included transient incontinence in 4 patients (6.6%) and mild perianal discomfort in 8 patients (13.3%). No serious complications occurred. Conclusion: BTX therapy is a safe, effective, and minimally invasive treatment for CAF, providing substantial pain relief and high healing rates with minimal complications. It represents a viable alternative for patients at high risk of postoperative incontinence. J Rang Med Col.2026 Mar;11(1): 141-145